A study on the achievement level of social skills objectives and outcomes in the preschool curriculum for six-year-olds - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
This study examines whether the objectives and outcomes related to the teaching of social skills in the preschool curriculum (for children aged 36-72 months) have an influence in social skill acquisition of six-year-old children. It was found that the activities based on the objectives and outcomes related to the teaching of social skills in the preschool curriculum (for children aged 36-72 months) were effective in the acquisition of social skills by preschool children. The difference between the children's pretest and posttest scores in the adaptation (Z=-4,205; p<,001), shyness (Z=-4,200; p<,001) and communication (Z=-4,208; p<,001) subdimensions of social skills was meaningful. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Preschool education; preschool curriculum; social skills; social competence; socialization